2014
DOI: 10.1176/appi.ps.201300136
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Mental Illness: Attitudes of Mental Health Professionals and the General Public

Abstract: Objectives The authors compared attitudes of the U.S. general public and of mental health professionals about the competence and perceived dangerousness of people with mental health problems and the desire for social distance from them. Factors related to negative attitudes and the desire for social distance also were examined. Methods Vignettes describing individuals meeting DSM-IV criteria for major depression and schizophrenia were included in the 2006 General Social Survey (GSS) and a 2009 study of menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 33 publications
7
90
0
11
Order By: Relevance
“…Their results supported earlier findings that knowledge of mental illnesses is not closely related to stigmatizing attitudes (Crisp, Gelder, Rix, Meltzer, & Rowlands, 2000). Similarly, Stuber et al (2014) reported that, although a sample of mental health professionals generally held more positive attitudes toward individual with mental illnesses than did the sample of individuals from the general public in their study, the mental health professionals were vulnerable to endorsement of negative social messages about mental illnesses.…”
Section: Social Distance Preferencesupporting
confidence: 81%
See 4 more Smart Citations
“…Their results supported earlier findings that knowledge of mental illnesses is not closely related to stigmatizing attitudes (Crisp, Gelder, Rix, Meltzer, & Rowlands, 2000). Similarly, Stuber et al (2014) reported that, although a sample of mental health professionals generally held more positive attitudes toward individual with mental illnesses than did the sample of individuals from the general public in their study, the mental health professionals were vulnerable to endorsement of negative social messages about mental illnesses.…”
Section: Social Distance Preferencesupporting
confidence: 81%
“…Stuber et al (2014) found, among a sample of 731 mental health service providers from 25 community mental health agencies, that having personal experience with mental illness, being a program manager (as opposed to front-line staff), and having more years of experience were predictors of more positive attitudes toward individuals with mental illnesses. This finding supports the suggestion that mental health service providers, depending on their job title, may spend a disproportionate amount of time in the company of individuals with mental illnesses when they are most unwell and when their engagement represents a hierarchical, rather than equal status, relationship (Bell et al, 2006 …”
Section: Familiarity With Mental Illnessmentioning
confidence: 97%
See 3 more Smart Citations